การเปลี่ยนแปลงเชิงพื้นที่ของชุมชนเมือง กรณีศึกษาชุมชนใต้จุดตัดทางด่วนศรีรัชและทางด่วนเฉลิมมหานคร - มณฑล เยี่ยมไพศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
To study the spatial transformation of urban communities underneath Srirat and Chalerm Mahanakhon expressway intersection, focusing on the change of transport network, land and building use including figure and ground patterns through time periods. This is to identify potentials as well as problems caused by the spatial transformation in relation to socioeconomic roles in order to use as basis information for the development planning of urban communities in the future. The study of the spatial transformation at the key three time periods has included the arrival of the elevated expressway structure as a barrier structure cutting through the communities. The result shows that as the structure just arrived, there was a pause of spatial development. Although the global spatial integration had increased, the movement network was not suitably fit with the existing accessible routes resulting in the blight of land and building use patterns in the area. As the communities had adjusted with the expressway structure due to its well integration with the urban area, the overall area has improved. There were evidences that the existing movement network has systematically adjusted with its surrounded context causing the renewal of commercial and residential districts and become more viable, leaving only some communities that have been directly affected by the physical structure of the expressway. These areas have become dilapidated and not lived up to their development potentials.